Pengaruh Kompensasi, Beban Kerja dan Lingkungan Kerja terhadap Komitmen Individu dengan Kepuasan Kerja sebagai Variabel Intervening - Tatawalat, Deswy; Anita Erari; Sarwo Edy Handoyo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the influence of compensation, workload, and work environment on individual commitment, with job satisfaction as an intervening variable, among contract employees at the Regional Secretariat of Boven Digoel Regency. The research employs a quantitative approach with a survey method, involving 100 contract employees selected through stratified random sampling. Data analysis is conducted using the Structural Equation Modeling (SEM) method with SmartPLS software. The results indicate that compensation, workload, and work environment significantly and positively influence individual commitment. Furthermore, job satisfaction serves as an intervening variable in the relationship between compensation, workload, and work environment with individual commitment. Hence, appropriate compensation, balanced workloads, and a conducive work environment can enhance job satisfaction, ultimately strengthening the individual commitment of contract employees. These findings provide implications for policymakers at the Regional Secretariat of Boven Digoel Regency in enhancing employee welfare and loyalty through more effective human resource management policies. Keywords: Compensation, Workload, Work Environment, Job Satisfaction, Individual Commitment